The outlaws Hennessey [large type] - Herzberg, Bob (Thorndike Press, a part of Gale, a Cengage Company, 2025)
"Outlaw violence and swift Western justice are about to collide... When farm boys Jed Tully and Ty Brody attempt to seek retribution against a greedy merchant by robbing his store one fateful night, they stumble upon a scene of chaos: the store already looted and its owner slain by the infamous Hennessey gang. Framed for the robbery and hunted for murder, Jed and Ty find themselves forced to flee from the law's grasp and seek refuge within the ranks of the very gang they hoped to defy. The Hennesseys' brutality, entanglement with corrupt authorities, and internal strife shatter the innocence of the two youths, plunging them into a maelstrom of violence and moral ambiguity. As they grapple with their newfound reality, Jed and Ty are faced with a daunting question. Can they retain their humanity amidst the chaos and muster the courage to confront the Hennessey gang, whose reign of terror threatens not only their own lives but the safety of their entire community?"--Publisher.